Metabolomic characterization of the chemical compositions of Dracocephalum rupestre Hance. (November 2022) - Gao, Jianjian; Wang, Zhe; Chen, Dan; Peng, Jiakun; Xie, Dongchao; Lin, Zhiyuan; Lin, Zhi; Dai, Weidong
Graphical abstract: Highlights: A comprehensive metabolomics study on Dracocephalum rupestre Hance (MJT). The effects of imitative green and black tea processing methods on MJT were studied. Flavones, flavanones, flavone/flavanone glycosides, and triterpenoids were characteristic compounds. Flavone/flavanone, lipids, and triterpenoids increased after processing. Flavone/flavanone glycosides degraded to flavone/flavanone after processing. Abstract: Maojian tea (MJT) is a traditional Chinese herbal tea beverage manufactured from the leaves of the Dracocephalum rupestre Hance plant. In this study, a nontargeted metabolomics approach combined with absolute quantifications was applied to comprehensively investigate the chemical compositions of MJT and to determine the effects of the processing methods on compounds. Flavones (apigenin and luteolin, 0.06–1.35 mg/g), flavanones (eriodictyol and naringenin, 0.1–2.3 mg/g), flavone 7-O-glycosides (0.15–5.98 mg/g), flavanone 7-O-glycosides (0.28–19.41 mg/g), and triterpenoids were presumed to be characteristic components of MJT. Applying imitative green and black tea processing methods to MJT led to increases in flavone/flavanone aglycones, lipids, and triterpenoids and decreases in flavone/flavanone glycosides, amino acids, organic acids, and most phenolic acids. This study offers novel insights into the chemical compositions and the influences of processing methods on MJT and will be utilized for the quality control of MJT.